Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Here are the solving steps for the problem.
Given:
[tex]\displaystyle \frac{-6}{4x}=12[/tex]
[1] Multiply both sides of the equation by 4x:
[tex]\displaystyle 4x(\frac{-6}{4x})=(12)4x[/tex]
-6 = 48x
[2] Divide both sides of the equation by 48:
[tex]\displaystyle \frac{-6}{48} = \frac{48x}{48}[/tex]
[tex]\displaystyle x=-\frac{1}{8}[/tex]
I am not sure how to solve the equation in one step, so here is it in two steps. My apologies.
Answer:
[tex] - \frac{1}{8} [/tex]
Step-by-step explanation:
The Algebraic Equation -6 divide by 4x = 12 can be stated mathematically as :
[tex] \frac{ - 6}{4x} = 12 \\ \\ cross \: multiplying \\ \\ 4x \: \times 12 = - 6 \\ \\ 48x = - 6 \\ dividing \: bothsides \: by \: 48 \\ \frac{48x}{48} = \frac{ - 6}{48} \\ \\ x = - \frac{1}{8} [/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.